Hire (Ujrah) In The Light Of Contemporary Islamic Jurisprudence - Abdulsoma, Thoarlim; Daud, Ismail; Razi, Yaakob; Wan Ismail, Wan Abdullah (2016)
Islam encourages seeking money and earning a living, as well as control of spending habit based on morals. Meanwhile, Islam forbids spending money through illegal means, and encourages spending for good; and established rules for financial transactions on the basis of consent. Ujrah (hire) is considered the most important issue in the life of the worker, and it is the focus of the relationship between the worker and the employer. It is lawful according to Islamic law. Ujrah (hire) is an agreement between the employer and the worker on exchange for payment of a sum of money as a reward for the work done. Islamic scholars have unanimously agreed that the reward which the people consider is either in cash or in-kind, or benefit. However, the scholars have different opinions regarding Ujrah Al-hijam (cupper hiring) and taking reward for teaching the Noble Qur’an. Reward is one of the pillars of contract; therefore the employer should pay the employee in time without delay. Also the jurists have different opinions regarding exchange of labour for food or clothing, or what is called Ijarah al-nafaqah (i.e, feeding in exchange for work). Islamic law established rules for determining the wages of workers in order to ensure appropriate amount of wage, so that it would enable workers and their families to access basic needs of life and to achieve equality between employers and workers. Meanwhile, we ask the Almighty Allah to make this study of benefit to researchers, and Muslim men and women.